War, peace, and violence: four Christian views - Copan, Paul. (Downers Grove, IL : : IVP Academic, An imprint of InterVarsity Press, 2022)
"In a world of war, terrorism, and constant threats to global stability, how should Christians honor Jesus Christ? Four experts in Christian ethics, political philosophy, and international affairs present four different views of just war, nonviolence, Christian realism, and church history, orienting readers to today's key positions"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher
Keywords: War -- Religious aspects -- Christianity; Just war doctrine; Violence -- Religious aspects -- Christianity; Peace -- Religious aspects -- Christianity